Submarine groundwater discharge in Dongshan Bay, China: A master regulator of nutrients in spring and potential national significance of small bays - Sun, Yafei; Wang, Guizhi; Weng, Yubin; Li, Qing; Zhang, Fei; Jiang, Weizhen; Dai, Guiyuan; Lin, Wen; Sun, Shengyao; Jiang, Yiyong; Zhang, Yuanjing (Frontiers in Marine Science, 2023)
We revealed that submarine groundwater discharge (SGD) predominately regulated nutrients distributions and fueled algal growth in Dongshan Bay, China based on mapping and time-series observations of Ra isotopes and nutrients, a case study of small bays (< 500 km2). On the bay-wide scale, the SGD rate was estimated to be 0.048 ± 0.022 m d-1 and contributed over 95% of the nutrients. At the time-series site where the bay-wide highest Ra activities in the bottom water marked an SGD hotspot with an average rate an order of magnitude greater, the maximum chlorophyll concentration co-occurred, suggesting that SGD may support the algal bloom. The ever most significant positive correlations between 228Ra and nutrients throughout the water column (P < 0.01, R2 > 0.90 except for soluble reactive phosphorus in the surface) suggested predominance of SGD in controlling nutrient distributions in the bay. Extrapolated to a national scale, the SGD-carried nutrient fluxes in small bays were 1.5 times as much as those in large bays (> 2000 km2). Thus, SGD-carried nutrients in small bays merit immediate attention in environmental monitoring and management.